Studi Kelayakan Bisnis Marigold Express Laundry - Dini Vientiany; Zahra Hasibuan; Silvia Meiliandari; Novri Salsabila (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of modern lifestyles has encouraged an increasing need for fast and practical laundry services. This article aims to examine the feasibility of Marigold Express Laundry, which is located in areas surrounding campuses and office districts in Medan City, through a business feasibility study approach. The analysis includes market and marketing aspects, legal aspects, technical and operational aspects, management, financial aspects, sharia principles, as well as social and environmental aspects. The method used in this study is a qualitative descriptive approach with a case study method through observation, interviews, and documentation. The results of the analysis indicate that Marigold Express Laundry has good market potential, an efficient operational system, a fairly structured management, and financially feasible conditions as reflected in its ability to cover operational costs and generate profits. Therefore, the business is considered feasible to be operated and developed.